Microcavity-Supported Lipid Bilayers; Evaluation of Drug-Lipid Membrane Interactions by Electrochemical Impedance and Fluorescence Correlation Spectroscopy - Ramadurai, Sivaramakrishnan (Langmuir : the ACS journal of surfaces and colloids, 2019)
Many drugs have intracellular or membrane-associated targets, thus understanding their interaction with the cell membrane is of value in drug development. Cell-free tools used to predict membrane interactions should replicate the molecular organization of the membrane. Microcavity array-supported lipid bilayer (MSLB) platforms are versatile biophysical models of the cell membrane that combine liposome-like membrane fluidity with stability and addressability. We used an MSLB herein to interrogate drug-membrane interactions across seven drugs from different classes, including nonsteroidal anti-inflammatories: ibuprofen (Ibu) and diclofenac (Dic); antibiotics: rifampicin (Rif), levofloxacin (Levo), and pefloxacin (Pef); and bisphosphonates: alendronate (Ale) and clodronate (Clo). Fluorescence lifetime correlation spectroscopy (FLCS) and electrochemical impedance spectroscopy (EIS) were used to evaluate the impact of drug on 1,2-dioleyl- sn-glycerophosphocholine and binary bilayers over physiologically relevant drug concentrations. Although FLCS data revealed Ibu, Levo, Pef, Ale, and Clo had no impact on lipid lateral mobility, EIS, which is more sensitive to membrane structural change, indicated modest but significant decreases to membrane resistivity consistent with adsorption but weak penetration of drugs at the membrane. Ale and Clo, evaluated at pH 5.25, did not impact the impedance of the membrane except at concentrations exceeding 4 mM. Conversely, Dic and Rif dramatically altered bilayer fluidity, suggesting their translocation through the bilayer, and EIS data showed that resistivity of the membrane decreased substantially with increasing drug concentration. Capacitance changes to the bilayer in most cases were insignificant. Using a Langmuir-Freundlich model to fit the EIS data, we propose Rsat as an empirical value that reflects permeation. Overall, the data indicate that Ibu, Levo, and Pef adsorb at the interface of the lipid membrane but Dic and Rif interact strongly, permeating the membrane core modifying the water/ion permeability of the bilayer structure. These observations are discussed in the context of previously reported data on drug permeability and log P